Attachment insecurity as a mediator of the relationship between childhood trauma and adult dissociation. Issue 2 (15th March 2018) - Kong, Seong Sook; Kang, Dae Ryong; Oh, Min Jung; Kim, Nam Hee
ABSTRACT: This study aimed to investigate whether attachment insecurity mediates the relationship between childhood trauma and adult dissociation, specifically with regard to individual forms of childhood maltreatment. Psychiatric outpatients who visited a specialized trauma clinic ( n  = 115) participated in the study. Data were collected via the Childhood Trauma Questionnaire, Revised Adult Attachment Scale, and Dissociative Experience Scale. Structural equation modeling and path analysis were performed to analyze the mediating effects of attachment insecurity on the relationship between childhood trauma and adult dissociation. Greater childhood trauma was associated with higher dissociation, and the relationship between them was fully mediated by attachment anxiety. In path analysis of trauma subtypes, the effects of emotional abuse, physical abuse, and physical neglect as a child on adult dissociation were found to be fully mediated by attachment anxiety. The effect of sexual abuse on dissociation was mediated by a synergistic effect from both attachment anxiety and attachment avoidance. Regarding emotional neglect, a countervailing interaction was discovered between the direct and indirect effects thereof on dissociation; the indirect effect of emotional neglect on dissociation was partially mediated by attachment insecurity. Specific aspects of attachment insecurity may help explain the relationships between individual forms of childhood trauma and adult dissociative symptoms. Tailored treatments based on affected areas of attachment insecurity may improve outcomes among patients with dissociative symptoms and a history of childhood trauma.